Cytokine/Chemokine/Growth Factor Profiles Contribute to Understanding the Pathogenesis of the Salivary Gland Dysfunction in Euthyroid Hashimoto’s Thyroiditis Patients - K. Morawska; M. Maciejczyk; S. Zięba; Ł. Popławski; A. Kita-Popławska; J. Krętowski; A. Zalewska (Mediators of Inflammation)
Hashimoto’s thyroiditis (HT) is one of the most common autoimmune diseases. It is suggested that, in addition to thyroid gland dysfunction, HT is responsible for impaired secretion from the salivary glands. The aim of this study was to evaluate the extent of symptoms of salivary gland dysfunction. We also assessed the relationship between the levels of selected cytokines, chemokines, and growth factors in unstimulated whole saliva (UWS) and the rate of UWS secretion and symptoms of xerostomia in HT patients. The study group consisted of 25 female patients diagnosed with Hashimoto’s disease in its spontaneous euthyroid state who had never received hormonal treatment. In more than half of the examined patients, we observed the level of UWS secretion below 0.2 mL/min, indicating impaired secretory function of the salivary glands. Moreover, we demonstrated that the clinical symptoms of salivary gland dysfunction worsen with disease duration. Nevertheless, the inflammatory changes occurring in these glands are independent of general inflammation in the course of HT. Our results clearly indicate an abnormal profile of cytokines, chemokines, and growth factors in the UWS of HT euthyroid women as well as the fact that concentrations of IL-6 and IL-1 as well as INF-γ, TNF-α, and IL-12 may be potential biomarkers for salivary gland dysfunction in the course of HT. Furthermore, salivary IL-12 (p40) may be helpful in assessing the progression of autoimmunity-related inflammation in the course of HT. In conclusion, secretory dysfunction of the salivary glands is closely related to autoimmunity-related inflammation in the course of HT, which leads to objective and subjective symptoms of dry mouth.